Corporate governance and financial misstatement: evidence from Vietnam. (15th February 2021) - Cao, Kien; Tran, Thao; Nguyen, Thuy
This study examines the influence of corporate governance on the likelihood of financial misstatement in Vietnam. Given the unique setting in Vietnam, financial misstatement information is manually collected from income statement figures in the reporting period between the pre-audit/pre-review date and post-audit/post-review date. The results indicate that, among various corporate governance variables, only ownership structure influences the likelihood of financial misstatement in Vietnam. Specifically, the state ownership has a positive impact and the foreign ownership has a negative impact on the likelihood of financial misstatement. The results indicate that, in a weak corporate governance structure, the participation of foreign investors has a huge impact in controlling the correctness of financial statements.